High-strength heat-resistant phenolic cotton cloth laminated board and preparation method thereof
By using block copolymerization of phenolic resin and epoxy resin and composite additives, combined with a two-step hot pressing process, the problems of high brittleness and insufficient toughness of phenolic resin were solved, and the preparation of high-strength and heat-resistant phenolic cotton fabric laminates was achieved.
Patent Information
- Application Number
- CN202511803694.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-12-03
- Publication Date
- 2026-02-06
AI Technical Summary
Traditional phenolic resins are brittle and lack toughness, making it difficult for their laminated products to meet the high requirements of application scenarios in terms of impact strength and interlaminar shear strength. At the same time, there is room for improvement in their residual carbon rate and strength retention rate at high temperatures.
A high-strength, heat-resistant phenolic cotton fabric laminate was prepared by block copolymerization of phenolic resin and epoxy resin using a chemical method, adding composite additives such as nano-silica, silane coupling agent and polyimide powder, and then using a two-step hot pressing process.
It significantly improves the toughness and strength of the laminate, maintains heat resistance, and retains good structural stability and flame retardant properties at high temperatures.
Smart Images

Figure CN121469112A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer composite materials technology, and in particular to a high-strength heat-resistant phenolic cotton laminate and its preparation method. Background Technology
[0002] Phenolic cotton laminate is a thermosetting composite material with cotton fabric as reinforcement and phenolic resin as matrix. Due to its excellent mechanical strength, electrical insulation, ablation resistance, and cost advantages, it is widely used in gears, bearings, and insulating structural components in the machinery, electronics, and aerospace industries.
[0003] However, traditional phenolic resins inherently suffer from high brittleness and insufficient toughness, making it difficult for their laminated products to meet the impact strength and interlaminar shear strength requirements of more demanding applications. Furthermore, while phenolic resins themselves have good heat resistance, there is still room for improvement in their char retention and strength retention at high temperatures. The high crosslinking density and rigid molecular chains of cured phenolic resin products are the main causes of their brittleness.
[0004] To improve toughness, existing technologies often employ physical blending or chemical modification methods. For example, while toughening with rubber elastomers can improve toughness, it often sacrifices the material's modulus, strength, and heat resistance. Epoxy resins, with their excellent adhesion and certain toughness, are one of the ideal candidates for modifying phenolic resins. However, simple physical blending may lead to poor compatibility, limited modification effects, and may introduce new problems such as decreased heat resistance.
[0005] Therefore, developing a laminate preparation technology that achieves chemical modification of phenolic resin through molecular design and is supplemented with efficient additives to significantly improve its toughness and strength without significantly losing or even simultaneously improving its heat resistance has important industrial application value. Summary of the Invention
[0006] The purpose of this invention is to address the shortcomings of existing technologies by proposing a high-strength, heat-resistant phenolic cotton laminate and its preparation method.
[0007] To achieve the above objectives, the present invention adopts the following technical solution:
[0008] This invention provides a high-strength, heat-resistant phenolic cotton laminate, which is produced by hot pressing multiple layers of cotton fabric impregnated with an epoxy-modified phenolic resin solution. The epoxy-modified phenolic resin solution comprises the following components in parts by weight:
[0009] Epoxy-modified phenolic resin: 100 parts;
[0010] Compound additives: 3-10 parts;
[0011] Hardener: 5-15 parts;
[0012] Solvent: 100~130 parts.
[0013] This invention provides a method for preparing the above-mentioned high-strength heat-resistant phenolic cotton laminate, comprising the following steps:
[0014] S1. Synthesis of epoxy-modified phenolic resin: Linear phenolic resin, epichlorohydrin, and a first catalyst are added to a reactor and stirred at 90-110℃ and 200-400 rpm for 2-4 hours to generate a phenolic epoxy resin intermediate. The temperature is then lowered to 70-80℃, and bisphenol A type epoxy resin and a second catalyst are added. Stirring continues at 200-400 rpm for 1-3 hours. Excess epichlorohydrin is removed by vacuum distillation to obtain a viscous epoxy-modified phenolic resin. The chemical reaction equation is as follows: Figure 1 As shown;
[0015] S2. Preparation of adhesive solution: Dissolve the epoxy-modified phenolic resin in S1 in a solvent and stir at 300-500 rpm for 30-60 minutes at room temperature until the resin is completely dissolved. Then, slowly add the curing agent and continue stirring at the same speed for 20-30 minutes until the curing agent is completely dissolved. Finally, add the composite additive and increase the stirring speed to 1000-2000 rpm. High-speed shear dispersion for 1-2 hours until a uniform and stable impregnation adhesive solution is obtained.
[0016] S3. Cotton fabric pretreatment: After degreasing, the cotton fabric is treated in a nitrogen plasma device for 3-8 minutes with a treatment power of 300-500W to form a microporous structure on the surface of the cotton fabric.
[0017] S4. Impregnation and drying: Impregnate the S3 cotton cloth in the S2 adhesive solution using an impregnation machine. Then, send the impregnated cloth into the drying channel. The total travel time of the cloth in the drying channel is 2 to 5 minutes, so that the solvent can fully evaporate and the resin can reach the partial gelation stage, resulting in a prepreg cloth with suitable viscosity and flowability.
[0018] S5. Lamination and Hot Pressing: The multi-layer prepreg fabric of S4 is stacked and placed in a mold preheated to 140~150℃. Hot pressing is performed on a hot press. First, the pressure is increased to 5~10MPa within 3 minutes, and the temperature and pressure are maintained at 150~160℃ for 20~40 minutes to allow the resin to flow and impregnate fully. Then, the temperature is increased to 170~185℃ at a heating rate of 1~2℃ / min, while the pressure is increased to 10~15MPa. The temperature and pressure are maintained for another 40~60 minutes to allow the resin to cure completely. After hot pressing, the pressure is maintained, and the mold is allowed to cool to below 60℃ before the pressure is released and the mold is demolded to obtain the high-strength heat-resistant phenolic cotton fabric laminate.
[0019] Preferably, the linear phenolic resin in step S1 is 2402, which does not contain curing agent and is produced by Shanghai Potential Chemical Co., Ltd. It is mixed with epichlorohydrin at a mass ratio of 1:6~10. The bisphenol A type epoxy resin is E-51, with an epoxy equivalent of 184~190g / eq. The amount of bisphenol A type epoxy resin used is 30%~50% of the mass of the linear phenolic resin.
[0020] Preferably, in step S1, the first catalyst is tetraethylammonium bromide, and its amount is 1% to 3% of the mass of linear phenolic resin; the second catalyst is 2-methylimidazole, and its amount is 0.1% to 1% of the total mass of linear phenolic resin and bisphenol A epoxy resin.
[0021] Preferably, the solvent in step S2 is a mixture of ethanol and acetone in a volume ratio of 1 to 3:1, and the amount of solvent used is 100% to 130% of the mass of the epoxy-modified phenolic resin.
[0022] Preferably, the curing agent in step S2 is at least one of hexamethylenetetramine and p-toluenesulfonic acid.
[0023] Preferably, the composite additive in step S2 is composed of nano-sized silica: silane coupling agent: polyimide powder in a mass ratio of 2~4:1~2:1; the particle size of the nano-sized silica is 10~50nm, the silane coupling agent is KH-550 (γ-aminopropyltriethoxysilane), and the particle size of the polyimide powder is less than 20μm.
[0024] Preferably, the cotton fabric in step S3 is a blend of cotton and polyester fibers with a blending ratio of 6:4, and the blended fabric is pretreated with KH-570 silane coupling agent.
[0025] Preferably, in step S4, the resin content accounts for 40% to 50% of the weight of the dried adhesive tape, the cotton cloth travels at a speed of 1.5 to 4.0 m / min, and the cotton cloth is immersed in the adhesive solution for 20 to 90 seconds. The drying channel is divided into three sections: the temperature of the first section is 100 to 110°C, the temperature of the second section is 115 to 125°C, and the temperature of the third section is 125 to 130°C.
[0026] Compared with the prior art, the beneficial effects of the present invention are:
[0027] 1. By using chemical methods to block copolymerize phenolic resin and epoxy resin, molecular-level composites are achieved. This retains the heat resistance of phenolic resin while introducing flexible segments of epoxy resin, fundamentally improving the toughness of the resin matrix.
[0028] 2. Synergistic effect of composite additives: Nano-silica, as rigid particles, not only plays a traditional reinforcing role but also absorbs impact energy through microcracks and plastic deformation, thus achieving toughening. Silane coupling agents effectively coat nano-silica and form strong chemical bonds between it and the resin matrix, greatly improving interfacial adhesion strength and preventing stress concentration. Polyimide powder, as an ultra-high heat-resistant polymer, is uniformly dispersed in the phenolic resin network, effectively supporting the structure at high temperatures and significantly improving the high-temperature strength retention and thermal stability of the laminate.
[0029] 3. The two-step hot pressing process makes the resin flow, wetting, gelation and curing process smoother and more complete, reducing internal defects and stress, and ensuring the uniformity and stability of the product performance. Attached Figure Description
[0030] Figure 1 This is the synthesis reaction equation for the epoxy-modified phenolic resin proposed in this invention. Detailed Implementation
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with existing known technologies. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0032] Example 1: A method for preparing a high-strength, heat-resistant phenolic cotton laminate, comprising the following steps:
[0033] S1. Synthesis of epoxy-modified phenolic resin: In a four-necked flask equipped with a stirrer, condenser, and thermometer, 100g of 2402 linear phenolic resin, 800g of epichlorohydrin, and 2g of tetraethylammonium bromide (the first catalyst) were added. The mixture was heated to 100℃ and stirred at 300rpm for 3h. Then, the temperature was lowered to 75℃, and 40g of E-51 type epoxy resin and 0.28g of 2-methylimidazole (the second catalyst) were added. The mixture was stirred at 300rpm for another 2h. After the reaction was complete, excess epichlorohydrin was recovered by vacuum distillation to obtain a viscous epoxy-modified phenolic resin.
[0034] S2. Preparation of adhesive solution: Take 100g of the above-mentioned S1 synthetic resin and dissolve it in a mixed solvent of 120g ethanol and acetone in a volume ratio of 2:1. Stir at room temperature and 400rpm for 40min until completely dissolved. Add 10g of curing agent hexamethylenetetramine and stir at 400rpm for 25min. Add 6g of composite additive (including 3g of nano silica, 1.5g of KH-550 silane coupling agent, and 1.5g of polyimide powder). Increase the stirring speed to 1500rpm and disperse for 1.5h to obtain the impregnation adhesive solution.
[0035] S3. Cotton fabric pretreatment: After degreasing, the cotton fabric is treated in a nitrogen plasma device for 5 minutes with a treatment power of 350~450W to form a microporous structure on the surface of the cotton fabric.
[0036] S4. Impregnation and Drying: The S3 cotton fabric is impregnated in the S2 adhesive solution using an impregnation machine at a speed of 2.5 m / min for 60 seconds. The resin content of the fabric is 45%. The impregnated fabric is then sent into the drying channel, where the temperature is set to 105-120-128℃ for 3 minutes to allow the solvent to fully evaporate and the resin to reach the partial gelation stage, resulting in a prepreg fabric with suitable viscosity and flowability.
[0037] S5. Lamination and Hot Pressing: Twelve sheets of S4 prepreg fabric are stacked and placed in a mold preheated to 145°C. Hot pressing is then performed on a hot press. First, the pressure is increased to 8MPa within 3 minutes and held at 155°C for 30 minutes to allow the resin to flow and impregnate fully. Then, the temperature is increased to 180°C at a heating rate of 15°C / min, while the pressure is increased to 12MPa. The temperature and pressure are held for another 50 minutes to allow the resin to fully cure. After hot pressing, the pressure is maintained, and the mold is allowed to cool to below 60°C before depressurization and demolding to obtain a high-strength, heat-resistant phenolic cotton fabric laminate.
[0038] Example 2: A method for preparing a high-strength, heat-resistant phenolic cotton fabric laminate, comprising the following steps:
[0039] S1. Synthesis of epoxy-modified phenolic resin: In a four-necked flask equipped with a stirrer, condenser, and thermometer, 100g of 2402 linear phenolic resin, 700g of epichlorohydrin, and 2g of tetraethylammonium bromide (the first catalyst) were added. The mixture was heated to 100℃ and stirred at 300rpm for 3h. Then, the temperature was lowered to 75℃, and 40g of E-51 type epoxy resin and 0.28g of 2-methylimidazole (the second catalyst) were added. The mixture was stirred at 300rpm for another 2h. After the reaction was complete, excess epichlorohydrin was recovered by vacuum distillation to obtain a viscous epoxy-modified phenolic resin.
[0040] S2. Preparation of adhesive solution: Take 100g of the above-mentioned S1 synthetic resin and dissolve it in a mixed solvent of 120g ethanol and acetone in a volume ratio of 2:1. Stir at room temperature and 400rpm for 40min until completely dissolved. Add 10g of curing agent hexamethylenetetramine and stir at 400rpm for 25min. Add 8g of composite additive (including 4g of nano silica, 2.4g of KH-550 silane coupling agent, and 1.6g of polyimide powder). Increase the stirring speed to 1500rpm and disperse for 1.5h to obtain the impregnation adhesive solution.
[0041] S3. Cotton fabric pretreatment:
[0042] After degreasing, the cotton fabric is treated in a nitrogen plasma device for 5 minutes with a processing power between 350 and 450W to form a microporous structure on the surface of the cotton fabric.
[0043] S4. Impregnation and Drying: The S3 cotton fabric is impregnated in the S2 adhesive solution using an impregnation machine at a speed of 2.5 m / min for 60 seconds. The resin content of the fabric is 45%. The impregnated fabric is then sent into the drying channel, where the temperature is set to 105-120-128℃ for 3 minutes to allow the solvent to fully evaporate and the resin to reach the partial gelation stage, resulting in a prepreg fabric with suitable viscosity and flowability.
[0044] S5. Lamination and Hot Pressing: Twelve sheets of S4 prepreg fabric are stacked and placed in a mold preheated to 145°C. Hot pressing is then performed on a hot press. First, the pressure is increased to 8MPa within 3 minutes and held at 155°C for 30 minutes to allow the resin to flow and impregnate fully. Then, the temperature is increased to 175°C at a rate of 15°C / min, while the pressure is increased to 12MPa. The temperature and pressure are held for another 50 minutes to allow the resin to fully cure. After hot pressing, the pressure is maintained, and the mold is allowed to cool to below 60°C before depressurization and demolding to obtain a high-strength, heat-resistant phenolic cotton fabric laminate.
[0045] Example 3: A method for preparing a high-strength, heat-resistant phenolic cotton fabric laminate, comprising the following steps:
[0046] S1. Synthesis of epoxy-modified phenolic resin: In a four-necked flask equipped with a stirrer, condenser, and thermometer, 100g of 2402 linear phenolic resin, 800g of epichlorohydrin, and 2g of tetraethylammonium bromide (the first catalyst) were added. The mixture was heated to 100℃ and stirred at 300rpm for 3h. Then, the temperature was lowered to 75℃, and 30g of E-51 type epoxy resin and 0.28g of 2-methylimidazole (the second catalyst) were added. The mixture was stirred at 300rpm for another 2h. After the reaction was complete, excess epichlorohydrin was recovered by vacuum distillation to obtain a viscous epoxy-modified phenolic resin.
[0047] S2. Preparation of adhesive solution: Take 100g of the above-mentioned S1 synthetic resin and dissolve it in a mixed solvent of 100g ethanol and acetone in a volume ratio of 2:1. Stir at room temperature and 400rpm for 40min until completely dissolved. Add 10g of curing agent hexamethylenetetramine and stir at 400rpm for 25min. Add 6g of composite additive (including 3g of nano silica, 1.5g of KH-550 silane coupling agent, and 1.5g of polyimide powder). Increase the stirring speed to 1500rpm and disperse for 1.5h to obtain the impregnation adhesive solution.
[0048] S3. Cotton fabric pretreatment: After degreasing, the cotton fabric is treated in a nitrogen plasma device for 5 minutes with a treatment power of 350~450W to form a microporous structure on the surface of the cotton fabric.
[0049] S4. Impregnation and Drying: The S3 cotton fabric is impregnated in the S2 adhesive solution using an impregnation machine at a speed of 2.5 m / min for 60 seconds. The resin content of the fabric is 45%. The impregnated fabric is then sent into the drying channel, where the temperature is set to 105-120-128℃ for 3 minutes to allow the solvent to fully evaporate and the resin to reach the partial gelation stage, resulting in a prepreg fabric with suitable viscosity and flowability.
[0050] S5. Lamination and Hot Pressing: Twelve sheets of S4 prepreg fabric are stacked and placed in a mold preheated to 145°C. Hot pressing is then performed on a hot press. First, the pressure is increased to 10MPa within 3 minutes and held at 160°C for 30 minutes to allow the resin to flow and impregnate fully. Then, the temperature is increased to 180°C at a heating rate of 15°C / min, while the pressure is increased to 12MPa. The temperature and pressure are held for another 50 minutes to allow the resin to fully cure. After hot pressing, the pressure is maintained, and the mold is allowed to cool to below 60°C before depressurization and demolding to obtain a high-strength, heat-resistant phenolic cotton fabric laminate.
[0051] Comparative Example 1: Compared with Example 1, this comparative example does not undergo epoxy modification. Instead, 100g of 2402 linear phenolic resin is used to replace the epoxy-modified phenolic resin synthesized in S1. The phenolic resin is dissolved in a solvent, a small amount of curing agent p-toluenesulfonic acid is added, and no composite additives are added. The traditional one-step hot pressing process is used. The pressure is increased to 10MPa within 3 minutes, and then the temperature is directly increased to 175°C and maintained at this temperature and pressure for 60 minutes. The remaining components and preparation process are exactly the same to prepare a phenolic cotton fabric laminate.
[0052] Comparative Example 2: Compared with Example 1, this comparative example only carried out the first step of reaction S1, and stopped after synthesizing the phenolic epoxy intermediate. Bisphenol A epoxy resin was not added for the second step of block copolymerization. The remaining components and preparation process were exactly the same, and phenolic cotton fabric laminate was prepared.
[0053] Comparative Example 3: Compared with Example 1, this comparative example does not add composite additives (nano silica, KH-550 silane coupling agent, polyimide powder) in S2, and the remaining components and preparation process are exactly the same to prepare phenolic cotton fabric laminate.
[0054] Comparative Example 4: Compared with Example 1, this comparative example only added nano-silica and polyimide powder to the composite additive in S2, without adding silane coupling agent KH-550. The remaining components and preparation process were exactly the same, and phenolic cotton fabric laminate was prepared.
[0055] Comparative Example 5: Compared with Example 1, this comparative example only added nano-silica and silane coupling agent KH-550 to the composite additive in S2, without adding polyimide powder. The remaining components and preparation process were exactly the same, and phenolic cotton fabric laminate was prepared.
[0056] Comparative Example 6: Compared with Example 1, the S4 hot pressing process was changed to the traditional one-step method, directly applying 12MPa pressure, raising the temperature from room temperature to 180°C, and holding the temperature and pressure for 80 minutes. The remaining components and preparation process were exactly the same, and phenolic cotton fabric laminate was prepared.
[0057] Performance testing: The phenolic cotton fabric laminates of Examples 1-3 and Comparative Examples 1-6 were subjected to the following performance tests:
[0058] 1. Bending strength: Referring to ASTM D790, "Standard Test Method for Bending Properties of Plastics and Electrical Insulators", a universal testing machine is used. The laminate is cut into strips of specified dimensions (usually 80mm x 10mm x 4mm), placed on two supports, and a load is applied in the middle through a three-point bending device until the sample breaks. The bending strength is calculated by the maximum load, span, and sample size. This index reflects the rigidity or bending resistance of the material.
[0059] 2. Impact strength: Referring to ASTM D256 "Standard Test Method for Cantilever Beam Impact Resistance of Plastics", a pendulum impact testing machine is used. The specimen with a specified notch (such as a V-notch) is placed horizontally on the support of the testing machine, and the pendulum is released to impact the specimen. The impact strength is calculated by the energy difference before and after the pendulum impact and the cross-sectional area at the notch of the specimen. This index reflects the toughness or impact resistance of the material.
[0060] 3. Heat distortion temperature: Referring to ASTM D648, "Standard Test Method for Heat Deformation of Plastics under Bending Load", a heat distortion temperature tester is used. The sample (usually 127mm x 13mm x 3mm) is placed in a silicone oil bath, and a specified bending stress (e.g., 1.82 MPa or 0.45 MPa) is applied. The temperature is increased at a constant rate (e.g., 2℃ / min). The heat distortion temperature is defined as the temperature at which the sample bends to a specified amount (e.g., 0.25mm). This indicator reflects the short-term heat resistance of the material under load.
[0061] 4. 250℃ / 100h Strength Retention Rate: Referring to ASTM D3045 "Standard Implementation Procedure for Thermal Aging of Plastics under No-Load Conditions", a thermal aging test chamber was used to subject the samples to long-term thermal exposure at a specified temperature (250°C in this case) and a specified time (100h in this case). Before and after aging, the strength was tested according to ASTM D790 (Flexural Strength) standard. The result was calculated as the percentage of the strength after aging to the initial strength. This indicator is used to evaluate the long-term thermal stability and service life of the material.
[0062] 5. Flame retardancy: Referring to UL 94 "Tests on flammability of plastic materials used in components of equipment and appliances", a horizontal and vertical burning tester is used. The sample is fixed vertically, and the lower end is burned with a Bunsen burner flame for 10 seconds. After removing the flame, the afterflame time is recorded. This process is repeated once, and the rating is determined based on the total afterflame time of the two tests and whether the absorbent cotton is ignited. V-0 is one of the highest ratings (short afterflame time, no dripping of flammable material).
[0063] 6. Water absorption rate: Refer to ASTM D570 "Standard Test Method for Water Absorption of Plastics". After drying the sample, weigh it and immerse it in distilled water at (23±0.5)℃ for 24 hours. After removing it and wiping off the surface moisture, weigh it immediately. The water absorption rate is calculated as the percentage of the weight difference before and after immersion to the dry weight. This index reflects the water resistance and dimensional stability of the material.
[0064] The test results are shown in Table 1 below:
[0065] Table 1. Effects of different formulations and process parameters on the performance of phenolic cotton laminate
[0066]
[0067] Data Analysis:
[0068] 1. Significantly Improved Mechanical Properties: As shown in Table 1, the laminates prepared in Examples 1-3 of this invention all exhibit flexural strengths exceeding 140 MPa and impact strengths exceeding 30 kJ / m², far superior to the samples of Comparative Example 1 (unmodified phenolic resin) and Comparative Example 2 (not fully block copolymerized). This result fully demonstrates that the two-step synthesis of epoxy-modified phenolic resin as the matrix successfully incorporates the toughness of bisphenol A type epoxy resin into the rigid network of phenolic resin, achieving a good balance between material rigidity and toughness, fundamentally overcoming the brittleness defect of traditional phenolic resins.
[0069] 2. Excellent Heat Resistance and Long-Term Thermal Stability: Regarding heat resistance, the heat distortion temperatures of all embodiments of this invention are above 180℃, indicating excellent short-term heat resistance. More importantly, after 100 hours of heat aging at 250℃, the flexural strength retention rates of Examples 1-3 are all above 80%, demonstrating extremely excellent long-term thermal stability. In contrast, the strength retention rate of Comparative Example 6 (using a one-step hot-pressing process) is only 55%. This indicates that the two-step hot-pressing process used in this invention (first low-temperature, low-pressure flow impregnation, then high-temperature, high-pressure curing) is crucial for forming a complete and stable cross-linked network, effectively avoiding the problem of a sharp decline in thermal aging performance caused by insufficient resin flow and numerous internal defects.
[0070] 3. Key Synergistic Reinforcing Effect of Composite Additives: By comparing the data of Comparative Example 3 (without any additives), Comparative Example 4 (without silane coupling agent KH-550), and Comparative Example 5 (without polyimide powder), it can be found that the lack of composite additives (Comparative Example 3) leads to a comprehensive decline in various properties. When silane coupling agent KH-550 is missing (Comparative Example 4), the water absorption rate of the laminate increases significantly (1.3% vs. 0.8% in Example 1), and the mechanical properties fail to reach the optimal level. This proves that KH-550 plays an irreplaceable role in improving the interfacial bonding between inorganic nanoparticles and organic resin, and enhancing the density and water resistance of the composite material. When polyimide powder is missing (Comparative Example 5), the long-term heat resistance (strength retention rate of 75%) and heat distortion temperature of the laminate decrease, proving the direct contribution of polyimide powder to improving the heat resistance of the system. In summary, nano-silica, KH-550 silane coupling agent, and polyimide powder constitute a synergistic reinforcement system, which works together from three aspects: particle reinforcement, interfacial coupling, and heat-resistant skeleton. This is a necessary condition for achieving the comprehensive performance of this invention.
[0071] 4. Top-tier flame retardant performance: Despite epoxy modification and the addition of multiple components, all embodiments achieved a UL 94 V-0 flame retardant rating, meeting the highest level of fire safety requirements. This demonstrates that the modified solution of this invention, while significantly improving mechanical and thermal properties, perfectly preserves the inherently excellent flame-retardant properties of phenolic resin.
[0072] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any equivalent substitutions or modifications made by those skilled in the art within the scope of the technology disclosed in the present invention, based on the technical solution and inventive concept of the present invention, should be covered within the scope of protection of the present invention.
Claims
1. A high-strength, heat-resistant phenolic cotton fabric laminate, characterized in that, It is prepared by hot pressing after impregnating multiple layers of cotton cloth with epoxy-modified phenolic resin solution; the epoxy-modified phenolic resin solution is made from raw materials containing the following components in parts by weight: Epoxy-modified phenolic resin: 100 parts; Compound additives: 3-10 parts; Hardener: 5-15 parts; Solvent: 100-130 parts; The epoxy-modified phenolic resin is prepared by the following method: Linear phenolic resin, epichlorohydrin, and a first catalyst are added to a reactor and stirred at 90-110°C and 200-400 rpm for 2-4 hours to generate a phenolic epoxy resin intermediate. After cooling to 70-80°C, bisphenol A type epoxy resin and a second catalyst are added, and the reaction is continued at 200-400 rpm for 1-3 hours. Excess epichlorohydrin is removed by vacuum distillation to obtain a viscous epoxy-modified phenolic resin.
2. The high-strength heat-resistant phenolic cotton laminate according to claim 1, characterized in that, The linear phenolic resin is 2402, which does not contain curing agent and is produced by Shanghai Potential Chemical Co., Ltd. It is mixed with epichlorohydrin at a mass ratio of 1:6~10. The bisphenol A type epoxy resin is E-51, with an epoxy equivalent of 184~190g / eq. The amount of bisphenol A type epoxy resin used is 30%~50% of the mass of the linear phenolic resin.
3. The high-strength heat-resistant phenolic cotton laminate according to claim 1, characterized in that, The first catalyst is tetraethylammonium bromide, and its dosage is 1% to 3% of the mass of linear phenolic resin; the second catalyst is 2-methylimidazole, and its dosage is 0.1% to 1% of the total mass of linear phenolic resin and bisphenol A epoxy resin.
4. The high-strength heat-resistant phenolic cotton laminate according to claim 1, characterized in that, The composite additive is composed of nano-sized silica, silane coupling agent and polyimide powder in a mass ratio of 2~4:1~2:1; the nano-sized silica has a particle size of 10~50nm, the silane coupling agent is γ-aminopropyltriethoxysilane, and the polyimide powder has a particle size of less than 20μm.
5. The high-strength heat-resistant phenolic cotton laminate according to claim 1, characterized in that, The solvent is a mixture of ethanol and acetone in a volume ratio of 1 to 3:1, and the amount of solvent used is 100% to 130% of the mass of the epoxy-modified phenolic resin.
6. The high-strength heat-resistant phenolic cotton laminate according to claim 1, characterized in that, The curing agent is at least one of hexamethylenetetramine and p-toluenesulfonic acid.
7. A method for preparing a high-strength heat-resistant phenolic cotton laminate as described in any one of claims 1 to 6, characterized in that, Includes the following steps: S1. Synthesis of epoxy-modified phenolic resin; S2. Preparation of adhesive solution: Dissolve the epoxy-modified phenolic resin in S1 in a solvent, stir at room temperature and 300-500 rpm for 30-60 minutes until dissolved, add the curing agent and continue stirring for 20-30 minutes until dissolved, finally add the composite additive, increase the stirring speed to 1000-2000 rpm, and disperse by high-speed shearing for 1-2 hours until a uniform and stable impregnation adhesive solution is obtained. S3. Cotton fabric pretreatment: After degreasing, the cotton fabric is treated in a nitrogen plasma device for 3-8 minutes with a treatment power of 300-500W to form a microporous structure on the surface of the cotton fabric. S4. Impregnation and drying: Impregnate the cotton fabric from S3 in the adhesive solution obtained from S2, control the resin content of the fabric after drying to be 40%~50%, and then pass it through a drying channel at 100~130℃ for 2~5 minutes to obtain the pre-impregnated fabric. S5. Lamination and Hot Pressing: The S4 multi-layer prepreg fabric is stacked and placed in a mold preheated to 140~150℃. First, it is kept at a pressure of 5~10MPa and a temperature of 150~160℃ for 20~40min. Then, the temperature is increased to 170~185℃ at a rate of 1~2℃ / min, while the pressure is increased to 10~15MPa. The heat and pressure are kept for another 40~60min. Finally, after cooling to below 60℃, the pressure is released and the mold is removed to obtain the high-strength heat-resistant phenolic cotton fabric laminate.
8. The method for preparing a high-strength heat-resistant phenolic cotton laminate according to claim 7, characterized in that, The cotton fabric described in S3 is a blend of cotton and polyester fibers with a blending ratio of 6:4, and the blended fabric is pretreated with KH-570 silane coupling agent.
9. The method for preparing a high-strength heat-resistant phenolic cotton laminate according to claim 7, characterized in that, In S4, the cotton cloth's travel speed is controlled at 1.5~4.0m / min, so that the cotton cloth is immersed in the adhesive solution for 20~90s. The drying channel is divided into three sections: the temperature of the first section is 100~110℃, the temperature of the second section is 115~125℃, and the temperature of the third section is 125~130℃.
10. The method for preparing a high-strength heat-resistant phenolic cotton laminate according to claim 7, characterized in that, The pressure in S5 rises to 5~10MPa within 3 minutes.